2017
DOI: 10.5588/ijtld.16.0428
|View full text |Cite
|
Sign up to set email alerts
|

Novel interferon-gamma assays for diagnosing tuberculosis in young children in India

Abstract: SUMMARY SETTING The tuberculin skin test (TST) and interferon-gamma release assays (IGRAs) are used as supportive evidence to diagnose active tuberculosis (TB). Novel IGRAs could improve diagnosis, but data are lacking in young children. DESIGN Children (age ≤ 5 years) with suspected TB were prospectively screened at a tertiary hospital in Pune, India; the children underwent TST, and standard (early secretory antigenic target 6 and culture filtrate protein 10) and enhanced (five additional novel antigens) e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…In this study, the prevalence of pulmonary tuberculosis among children is 5.73% (22/384), which is similar to the finding in Tanzania (5.2%). 34 However, it is higher than the findings reported in Zambia (1.58%), 35 Mozambique (1.65), 36 South Africa (1.3%), 37 and lower than reports from India (15%), 38 Zimbabwe (8.7%), 39 Greenland (8.5%), 40 South Africa (13%), 41 Uganda (10%), 42 Ethiopia (13.6%), 43 Bangladesh (32.97%) 44 and Nigeria (32%). 45 The reason for variation might be due to the difference in the prevalence of tuberculosis in the general population, methods of sputum sample collection and diagnosis.…”
Section: Discussionmentioning
confidence: 62%
“…In this study, the prevalence of pulmonary tuberculosis among children is 5.73% (22/384), which is similar to the finding in Tanzania (5.2%). 34 However, it is higher than the findings reported in Zambia (1.58%), 35 Mozambique (1.65), 36 South Africa (1.3%), 37 and lower than reports from India (15%), 38 Zimbabwe (8.7%), 39 Greenland (8.5%), 40 South Africa (13%), 41 Uganda (10%), 42 Ethiopia (13.6%), 43 Bangladesh (32.97%) 44 and Nigeria (32%). 45 The reason for variation might be due to the difference in the prevalence of tuberculosis in the general population, methods of sputum sample collection and diagnosis.…”
Section: Discussionmentioning
confidence: 62%
“…For example, first, age was associated with the IGRA results. [20][21][22] In addition, body mass index < 16.0 kg/m 2 ), HIV infection, race, HLA allele, and smoking habit were also associated with negative IGRA results. 6,15,23,24 Second, Sharninghausen et al 15 found that anemia (less hemoglobin) was an independent risk factor for an indeterminate IGRA result.…”
Section: Discussionmentioning
confidence: 98%
“…TB effectiveness for diagnosing pediatric tuberculosis as only adults were studied; substantial differences have been reported between immune responses to MTB in children versus adults. [ 41 , 42 ] Third, the impact of nontuberculous mycobacterial (NTM) infection was not considered here even though patients infected with M. kansasii, M. szulgai or M. marinum may also have positive IGRA results, since NTM also harbor genes encoding ESAT-6 and CFP-10 antigens. [ 7 ]…”
Section: Discussionmentioning
confidence: 99%